1996
DOI: 10.1002/j.1460-2075.1996.tb00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Tom7 modulates the dynamics of the mitochondrial outer membrane translocase and plays a pathway-related role in protein import.

Abstract: The preprotein translocase of the outer mitochondrial membrane is a multi‐subunit complex with receptors and a general import pore. We report the molecular identification of Tom7, a small subunit of the translocase that behaves as an integral membrane protein. The deletion of TOM7 inhibited the mitochondrial import of the outer membrane protein porin, whereas the import of preproteins destined for the mitochondrial interior was impaired only slightly. However, protein import into the mitochondrial interior was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
137
2
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(148 citation statements)
references
References 74 publications
(89 reference statements)
4
137
2
2
Order By: Relevance
“…A BLAST search of the nucleotide data base revealed a human cDNA with significant homology (47% similarity and 28% identity) with yeast Tom7 (18). The human cDNA contains a 165-bp ORF encoding a protein of 55 amino acids with a predicted molecular mass of 6.2 kDa.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A BLAST search of the nucleotide data base revealed a human cDNA with significant homology (47% similarity and 28% identity) with yeast Tom7 (18). The human cDNA contains a 165-bp ORF encoding a protein of 55 amino acids with a predicted molecular mass of 6.2 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…The human cDNA contains a 165-bp ORF encoding a protein of 55 amino acids with a predicted molecular mass of 6.2 kDa. An amino acid alignment of the human ORF with known Tom7 orthologs from the yeast S. cerevisiae, (18), N. crassa (39), and potato (Solanum tuberosum (40)) along with putative Tom7 proteins from Caenorhabditis elegans (GenBank TM accession number P34660) and mouse (Mus musculus, GenBank TM accession number W74865) revealed that they all contain the conserved motif aGaX-PXXXXXG where a is an aromatic residue and X is any residue (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tom5 was initially only identi ed in Saccharomyces cerevisiae, but recently has also been detected in Neurospora crassa (Neupert et al, unpublished). Tom6 and Tom7 seem to be involved in the regulation of the assembly and disassembly of receptor proteins with the GIP, a process that is probably mediated by Tom22 (41,48,(54)(55)(56)(57)(58). Recently it was shown in cross-linking experiments that Neurospora crassa Tom6 and Tom7 are in vicinity of preproteins, which are in transit across the outer membrane (58).…”
Section: Translocation Across the Outer Membranementioning
confidence: 99%